Porphyrin/SiO2/Cp*Rh(bpy)Cl Hybrid Nanoparticles Mimicking Chloroplast with Enhanced Electronic Energy Transfer for Biocatalyzed Artificial Photosynthesis. (7th December 2017) - Ji, Xiaoyuan; Wang, Jie; Mei, Lin; Tao, Wei; Barrett, Austin; Su, Zhiguo; Wang, Shaomin; Ma, Guanghui; Shi, Jinjun; Zhang, Songping
Abstract: A biocatalyzed artificial photosynthesis system (APS) based on porphyrin/SiO2 /Cp*Rh(bpy)Cl hybrid nanoparticles (TCPP/SiO2 /Rh HNPs) to mimic chloroplasts in green plant is reported. The TCPP/SiO2 /Rh HNPs are fabricated via sol–gel reaction of silica precursors functionalized with photosensitizer (porphyrin, TCPP) and electron mediator (Cp*Rh(bpy)Cl, M); while the integration of enzyme and coenzyme nicotinamide adenine dinucleotide (NAD)(H), on the outer surface of the HNPs is achieved through electrostatic‐interaction‐driven assembling under the entanglement of a negatively charged polyelectrolyte. The chloroplast‐mimicking, highly integrated APS exhibits remarkably superior performance over a free system such that the regeneration of NADH is improved from 11% to 75%, and the synthesis of formic acid from CO2 increased from 15 to 100 µmol. Based on the detailed investigations into the photochemical and electrochemical properties, it is speculated that the covalent linking of the photosensitizer and electron mediator via silicon hydride bonds, and the formed SiO2 network through sol–gel reaction, may form intramolecular and intermolecular electron transfer chains to direct more efficient electron transfer from TCPP to M. Such intramolecular and intermolecular electrons and energy transfer, cooperated with the integrated biocatalytic process, lead to the significantly enhanced overall reaction efficiency. Moreover, the integrated APS also allows facile recycling of expensive M, enzymes, and cofactors. Abstract : A chloroplast‐mimicking porphyrin (TCPP)/SiO2 /Cp*Rh(bpy)Cl hybrid nanoparticle based artificial photosynthesis system that can efficiently convert CO2 to formic acid under visible‐light irradiation is developed by sol–gel reaction with TCPP and electron‐mediator‐(M) functionalized silica precursors. The intramolecular and intermolecular electron transfer between photosensitizer and M and integration of whole system enable more efficient trafficking of chemicals and electron species between individual active components.